2019
DOI: 10.2499/p15738coll2.133523
|View full text |Cite
|
Sign up to set email alerts
|

Women’s empowerment, agricultural extension, and digitalization: Disentangling information and role model effects in rural Uganda

Abstract: established in 1975, provides researchbased policy solutions to sustainably reduce poverty and end hunger and malnutrition. IFPRI's strategic research aims to foster a climate-resilient and sustainable food supply; promote healthy diets and nutrition for all; build inclusive and efficient markets, trade systems, and food industries; transform agricultural and rural economies; and strengthen institutions and governance. Gender is integrated in all the Institute's work. Partnerships, communications, capacity str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The overall study took the form of a 3 3 factorial design (plus a separate pure control group), where one factor corresponds to the information technology and the other two factors varied the gender of the person to whom the video was shown within the household and the gender of the person providing the information in the video. In this study, we restrict attention to the first factor; for an analysis of the other factors, we refer to Lecoutere, Spielman, and Van Campenhout (2019). More information on the overall study can also be found in the pre-analysis plan, which was preregistered and publicly available from the American Economic Association's registry for randomized controlled trials (AEARCTR-0002153).…”
Section: Experimental Design and Estimation Of Treatment Effectsmentioning
confidence: 99%
“…The overall study took the form of a 3 3 factorial design (plus a separate pure control group), where one factor corresponds to the information technology and the other two factors varied the gender of the person to whom the video was shown within the household and the gender of the person providing the information in the video. In this study, we restrict attention to the first factor; for an analysis of the other factors, we refer to Lecoutere, Spielman, and Van Campenhout (2019). More information on the overall study can also be found in the pre-analysis plan, which was preregistered and publicly available from the American Economic Association's registry for randomized controlled trials (AEARCTR-0002153).…”
Section: Experimental Design and Estimation Of Treatment Effectsmentioning
confidence: 99%
“…They have fewer opportunities to join social networks and thus lack in monetary facilities more than male farmers. However, male farmers have a considerably higher level of access to agricultural information and participation in extension programs than women farmers (Lecoutere et al, 2019;Bahadurghartimagar, 2011). Godwin et al, 2018, has also reported that gender differences effect the use and accessibility of agricultural information sources.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additional studies such as [91] provided a gender experiment to improve new management practices of Ugandan women related to maize crops, sharing knowledge through informational videos which exposed an appropriate input use, and management practices using different strategies to obtain higher yields. Another study [92], explored the role WeChat played for 25 rural women from China, showing a variety of motivations for using this technological platform, such as promoting their traditional business through exhibiting their products, communicating with suppliers and customers, and learning strategies, signifying not only the opening of new learning and self-advancement oppurtunities, but also a tool for the construction of innovative female citizens.…”
Section: Literature Reviewmentioning
confidence: 99%